(untitled) (Research, Society and Development, 2022)
Mastitis is one of the main diseases that affects the dairy cattle, being caused by several microorganisms, which Staphylococcus aureus and Escherichia coli stand out. The usually treatment performed through using intramammary antibiotics. However, unappropriated use these drugs has contributed to selection resistant strains, became difficult the treatment and control of mastitis. Thereby, the objective is to evaluate strains S. aureus and E. coli against the antibiotics: Florfenicol, Enrofloxacin, Gentamicin, Amikacin, Tetracycline, Norfloxacin, Cephalothin, Cephalexin, Gentamicin, Neomycin, Amoxicillin, Ampicillin + Sulbactam, Cefoxitin, Bacitracin, Ampicillin and Penicillin. The bacteria were inoculated in 0.9% saline and seeded in 100 µL of Mueller Hinton medium with the antibiotic disks. The tests were performed in quadruplicate and plates were incubated at 37°C for 24h. Results showed that S. aureus was resistant to penicillin (10µg) and ampicillin (10µg), showing greater sensitivity to antibiotic florfenicol (30µg). Bacteria E. coli also showed greater sensitivity to florfenicol (30µg), being resistant to bacitracin (10µg). Our results indicated that search for new alternatives for treatment of mastitis is urgent and necessary.